UI/UX design in food health start up using design thinking method and gestalt principles - MA, M LUTFI (IndoCompt Publisher, 2025)
Healthy food is an absolute necessity and a primary need for human life. However, many foods are currently served in unhealthy ways, such as using raw materials, processing methods, and long storage times. A food retailer and food outlet must be able to meet the need for healthy food, both in terms of raw materials, processing methods, and storage times until it is served to consumers. The FoodHealth startup will provide a service for daily healthy food subscriptions for consumers. The research method used is the design thinking method, the analysis uses SWOT, the feasibility study analysis uses TELOS while User Interface has been created using the Gestalt principle. The UI design testing process uses 10 Usability Heuristic indicators with a test result of 83%. This proves that the designed digital start-up FoodHealth has answered user needs. This FoodHealth start-up is expected to provide convenience for users in finding information on healthy food programs or healthy food subscriptions, including ease of delivery.